2006
DOI: 10.1248/bpb.29.2226
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Spectrum of Plant Polyphenols and Extracts Depending upon Hydroxyphenyl Structure

Abstract: Recently, many biochemical and epidemiological studies have revealed that polyphenols of various foods and herbs have benefits to human health, and some extracts of polyphenol-rich plants, such as green tea and grape seed, have been added to foods or supplements. The antibacterial activity of various plant polyphenols and plant extracts have also been evaluated in several pharmaceutical studies. 1,2) Although tea polyphenols and their extracts have been examined in detail, [3][4][5][6] other extracts of polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
187
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(219 citation statements)
references
References 15 publications
25
187
4
3
Order By: Relevance
“…This impairment in drug diffusion is a major limitation in the evaluation of the antimicrobial effects of plant extracts using agar diffusion method (Esiome et al, 2006). The conclusion by Taguri et al (2006) that the antimicrobial potency of tea polyphenols is dependent upon bacterial species is consistent with the findings of this study, which showed that, the green and black tea extracts were more active against the Grampositive, S. aureus ATCC 25923 as compared to E. coli ATCC 25923 which is Gram-negative.…”
Section: Discussionsupporting
confidence: 91%
“…This impairment in drug diffusion is a major limitation in the evaluation of the antimicrobial effects of plant extracts using agar diffusion method (Esiome et al, 2006). The conclusion by Taguri et al (2006) that the antimicrobial potency of tea polyphenols is dependent upon bacterial species is consistent with the findings of this study, which showed that, the green and black tea extracts were more active against the Grampositive, S. aureus ATCC 25923 as compared to E. coli ATCC 25923 which is Gram-negative.…”
Section: Discussionsupporting
confidence: 91%
“…They also bind to adhesins, complex with cell wall and inactivate proteolytic macerating enzymes used by plant pathogens (Mohanta et al, 2007;Gurjar et al, 2012). From this it can be presumed that phenolic compounds act at two different points (cell membrane and cell wall), affecting the growth and metabolism of bacteria (Taguri et al, 2006;Stefanovic et al, 2012). Similar results have also been reported in other studies (Rajeshwar et al, 2005;Kuete et al, 2007).…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, the antibacterial activity of the two species may be explained by the total phenolics content. Many research reports reveal that phenolic compounds contribute to the antimicrobial properties of plant extracts whereby the extent of inhibition depends on the concentration of these compounds (Taguri et al, 2006;Rhouma et al, 2009;Rodriguez et al, 2009;Tian et al, 2009;Zongo et al, 2011;Moteriya et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity is the main type of their interactions [Funatogawa et al 2004, Taguri et al 2006. The effect of the presence of ellagitannins in bacteria has been examined and it has been found that the hydrolysable tannins have an antibacterial effect for a short time (up to seven days), regardless of their molecular weight , Kołodziej et al 2000.…”
Section: The Antimicrobial Activity Of Ellagitanninsmentioning
confidence: 99%